Topology and lattice optimization of 15-5PH stainless steel bracket - Mohd Fauzi, Nurul Qistina (2022)
The rising popularity of topology optimization continue to pave its ways into the manufacturing industry such as automotive, medical and aviation due to the increasing demand in lightweight structure with substantial amount of strength. Compared to the traditional method of manufacturing for aircraft component, the possibility of producing lightweight product s difficult due to longer design and manufacturing process as well as the acquired final complex shape that will make it impossible for the component to be fabricated through traditional manufacturing, Intensive research has been done by many researchers on the optimization of aircraft components. Therefore, the focus of this study is to take an airplane bearing bracket as a case study for topology optimization to determine material use, boundary and loading conditions. A volume constraint of 40 percent is implemented as the constraint for the airplane bracket with 15 -5PH stainless steel as the chosen material. Another optimization method with the used of lattice structure as the in-fill of the bracket is studied. With variant percentage of lattice in-fill from 50-100% is applied on the original model of the airplane bracket. The structural optimizations are carried out using commercial optimization software of Altair Inspire. Results found that topology optimization and lattice optimization were able to produce reliable and satisfactory results for the static loading conditions such as massive weight reduction, low displacement that contributes to stiffer material under the considered mechanical force as well as less stress concentration: compared to the original structure of the airplane bearing bracket. This research indicates that the integration of optimization design method such as topology and lattice optimization can be a powerful kit in serving as guidance for the engineers and designers searching for new featherweight design ideas without neglecting the strength of the aircraft at an early design stage.